Novel Eye Diagram Estimation Technique to Assess Signal Integrity in High-Speed Memory Test - Oh, Youngsu; Han, Dongmin; Go, Byeongseon; Lee, Seungtaek; Jeong, Woosik (Proceedings - International Test Conference, 2020)
This paper presents a method for the evaluation of the eye diagram of a signal by analyzing the atypical Shmoo plot extracted from an automatic test equipment using a loopback technique. The loopback technique was used to minimize the external noise generated by an oscilloscope, thereby making it easier to measure the signals and collect raw data. In addition, the Shmoo plot extracted using a shorting package enables analyses of the signals entering the device in actual situations. Subsequently, an analysis tool was developed to investigate characteristics of the extracted atypical Shmoo plot, such as jitter, rise and fall time, and signal data rate. Furthermore, this tool indicates the signal loss rate for all the pass zones and center point deviations in the eye diagram. The analysis tool produces an eye diagram from the extracted Shmoo plot to determine the signal quality status and also statistically analyzes the extracted raw data to determine the process capability of the automatic test equipment.